Hypericum empetrifolium subsp. empetrifolium: an assessment of its antifungal, antidiabetic, anti-aging, and neuroprotective potential - Demirci Kayıran, Serpil; Tavlı, Ömerül Faruk; Mataracı Kara, Emel; Kaplan, Alevcan; Şahin, Hasan; Boğa, Mehmet; Eroğlu Özkan, Esra (Frontiers in Pharmacology, 2025)
IntroductionHypericum empetrifolium subsp. empetrifolium Willd. (Hypericaceae), traditionally used in folk medicine, was investigated for its diverse biological activities. The study was driven by the increasing global health and economic burden posed by fungal infections, highlighting the urgent need for novel antifungal agents.MethodsPlant materials were collected from distinct regions in Türkiye. Methanolic extracts were prepared and tested in vitro for antimicrobial and enzyme inhibition activities. Minimum inhibitory concentration (MIC) and IC50 values were determined using standard microdilution and spectrophotometric assays. Phytochemical profiling of the extracts was performed using HPLC-DAD and LC-HR/MS to identify major chemical constituents and investigate variation due to geographic and environmental factors.Results:Methanolic extracts exhibited potent antifungal activity against Candida strains, with MIC values as low as 4.88 μg/mL. Enzyme inhibition assays revealed strong activity for HE-1, with IC50 values of 8.16 μg/mL for acetylcholinesterase and 2.46 μg/mL for butyrylcholinesterase. The extracts also significantly inhibited α-glucosidase (IC50 ≈ 26–31 μg/mL), outperforming acarbose, and showed moderate inhibition against elastase. Phytochemical profiling indicated notable variations in flavonoid and phenolic acid content, likely influenced by geographic and environmental factors.Discussion:These findings suggest that H. empetrifolium subsp. empetrifolium extracts possess promising antifungal, antidiabetic, anti-aging, and neuroprotective properties. The observed bioactivities and phytochemical richness support further exploration of this species as a potential source of therapeutic agents.